Childhood vaccination as a part of the National Immunization Schedule during the COVID-19: problems and potential solutions - A.A. Garina; A.L. Zaplatnikov; F.I. Petrovski; L.P. Tandalova (LCC «Medicine-Inform», 2021)
A.A. Girina1, A.L. Zaplatnikov2, F.I. Petrovskiy1, L.P. Tandalova3 1Khanty-Mansi State Medical Academy, Khanty-Mansiysk, Russian Federation 2Russian Medical Academy of Continuous Professional Education, Moscow,   Russian Federation 3District Clinical Hospital, Khanty-Mansiysk, Russian Federation Aim: to compare monthly implementation of immunization plan as a part of the National Immunization Schedule in 2019 and 2020 in children aged 0-18 years. Patients and Methods: monthly and annual form No. 5 "Information on prophylactic immunization" (from January 2019 to December 2020) was analyzed. Monthly implementation of immunization plan for each vaccine-preventable disease (whooping cough, poliomyelitis, mumps, rubella, measles, diphtheria tetanus and other) were analyzed separately. Results: in the beginning of the COVID-19 pandemic, a significant (8.8-fold) reduction in the coverage of children with immunization against vaccine-preventable diseases was reported compared to 2019 (р<0.0001). The reduction in the implementation of immunization schedule required urgent solutions to maintain a high level of herd immunity. The recovery of the required implementation of immunization plan against whooping cough and poliomyelitis was achieved by the end of 2020. The recovery of the required implementation of immunization plan against diphtheria and tetanus, measles, rubella, and mumps will be achieved in September 2020 (considering the National Immunization Schedule that includes revaccinations in preschool and school years). Conclusions: timely identification of the drawbacks of the organization of immunization and the prompt development of effective measures and implementation into clinical practice allowed for full implementation of immunization plan in children in 2020, despite the ongoing COVID-19 pandemic. Keywords: vaccination, children, National Immunization Schedule, revaccination, COVID-19 pandemic. For citation: Girina A.A., Zaplatnikov A.L., Petrovskiy F.I., Tandalova L.P. Childhood vaccination as a part of the National Immunization Schedule during the COVID-19: problems and potential solutions. Russian Journal of Woman and Child Health. 2021;4(1):85-89. DOI: 10.32364/2618-8430-2021-4-1-85-89.